ChemInform Abstract: Efficient Synthesis of Novel Thiazol‐2‐ylidene‐amides Using Carbonylthiourea Building Blocks. Issue 49 (December 2015) - Saeedi, Mina; Goli, Fereshteh; Mahdavi, Mohammad; Asadipour, Ali; Shafiee, Abbas; Foroumadi, Alireza
Abstract: Thiazolylideneamides are prepared by alkylation—cyclization reaction between thioureas and propargyl bromide in short reaction times and good yields.